THE CORRELATION BETWEEN MADRASAH PRINCIPAL LEADERSHIP AND CERTIFICATION INCENTIVES ON THE PERFORMANCE OF MADRASAH ELEMENTARY SCHOOL TEACHERS IN BINJAI CITY - Halim, Abdul; Wijaya, Candra; Fadhli, Muhammad (International Journal of Cultural and Social Science, 2025)
This study examines the relationship between the leadership of the head of Madrasah and the provision of certification incentives with teacher performance in Madrasah Ibtidaiyah in Binjai City. The research aims to determine if there is a positive relationship between the leadership of the head of Madrasah and teacher performance, the provision of certification incentives and teacher performance, and the combined effect of both leadership and certification incentives on teacher performance. The study employed a quantitative approach with a descriptive correlational design. The population consisted of 128 teachers, with a sample of 97 teachers selected for the study. Data was collected through questionnaires, which were pre-tested. Data analysis included descriptive statistics, correlation analysis, and regression analysis. The findings revealed a significant positive relationship between the leadership of the head of Madrasah and teacher performance (correlation coefficient = 0.364), the provision of certification incentives and teacher performance (correlation coefficient = 0.213), and both factors combined with teacher performance (correlation coefficient = 0.404).